Analysis of People’s Compliance with the Law in the Covid-19 Vaccination Program in Indonesia - Djayaputra, Dr.Gunawan (International Journal of Scientific Research and Management (IJSRM), 2021)
The implementation of the COVID-19 vaccination is very important because the 1945 Constitution Article 28 H Paragraph (1) and (2) mandates that everyone has the right to live in physical and mental prosperity, to live, and get a good and healthy living environment and the right obtain health services, and Law Number 32 of 2009 concerning Environmental Protection and Management. The purpose of this study is to investigate and analyze various laws and regulations related to public compliance with the law in implementing the Covid-19 vaccination program. This type of research is normative legal research, analyzing prevailing legal norms by examining library materials or secondary data, and primary data as a support. The findings of this research indicate that efforts to improve people's compliance with law through instrumental and normative perspectives as well as implementing and promoting Social inclusion is a critical issue to realize the successful implementation of the COVID-19 vaccination program in Indonesia.